Microsoft Excel: a tool for research. - Luis Orlando Pérez González (Medisur)
Frequently, our professionals in their research activity, lack of some knowledge and skills to deal with strong as well as complex statistical systems like SPSS; even these last are not available occasionally, and they have to look for other partners help. Besides, sometimes Microsoft Excel is undervaluated as a tool for research. This software could be of much help for this aim. Excel is basically an electronic calculation sheet, but it is much more, it is a very good option to solve most statistical needs in our researches.